Heterogeneous Patience, Population Growth, and Wealth Accumulation - Stéphane Bouché; Mikhail Pakhnin (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study a neoclassical growth model with population growth and agents who are heterogeneous in their discount factors. Population growth is interpreted as the entry of new infinitely-lived agents with zero initial endowments who are not included in the economic calculus of existing agents. We prove that when capital and labor are substitutes in production and utility is isoelastic, there exists a unique stationary equilibrium in per capita terms. A stationary equilibrium can take one of two forms: a Ramsey conjecture equilibrium, in which only the most patient agents own the entire capital stock, or a non-degenerate equilibrium, in which agents other than the most patient ones also hold positive amounts of capital. We show that introducing public debt, a labor income tax or a capital subsidy shifts the economy from a Ramsey conjecture stationary equilibrium to a non-degenerate one, and analyze the resulting relationship between income and inequality.
Keywords: D15; D31; D50; E21; O40; 330; economic growth; heterogeneous discounting; inequality; ramsey conjecture; overlapping generations